Friday

August 26, 2016
Posted by **TRIG HELP** on Monday, November 12, 2012 at 7:32am.

cos x/1+sinx + 1+ sinx/cosx = 2sec

- TRIG -
**Reiny**, Monday, November 12, 2012 at 7:50amin this case you must use brackets or else the statement is false

LS = cosx/(1+sinx) + (1+sinx)/cosx

= cosx/(1+sinx) + (1+sinx)/cosx

= ( cosx(cosx) + (1+sinx)(1+sinx) )/(cosx(1+sinx))

= (cos^2 x + 1 + 2sinx + sin^2 x)/(cosx(1+sinx))

= (1 + 1 + 2sinx)/(cosx(1+sinx))

= 2(1+sinx)/(cosx(1+sinx))

= 2/cosx

= 2secx

= RS